EFEKTIVITAS PENGGUNAAN TEKNIK PRESENTASI DAN PRAKTIKUM DALAM PEMBELAJARAN ACARA AGAMA HINDU PADA MAHASISWA PROGRAM STUDI PGSD SEMESTER III TAHUN AKADEMIK 2019/2020 - Putu Sanjaya (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
Learning outcomes largely determined by the learning process. A learning process that planned and implemented well will have an impact on achieving optimal learning outcomes. This paper reviews the effectiveness of the use of presentation techniques and practicum in learning (lectures) courses in Hindu Religious Events. The learning outcomes achieved by students classified as very good. That means that overall from the planning, implementation, to the evaluation stage has been carried out optimally.Keywords: Presentation And Practicum Techniques, Acara Hinduism, PGSD